Determination of serum cholesterol concentration in the presence of ascorbate. Issue 3 (March 1993) - Lumb, P J; Slavin, B M
Abstract : Pretreatment of a serum or plasma sample with ascorbate oxidase removed interfering ascorbate and allowed the determination of cholesterol to be carried out by a current enzymatic cholesterol method available in kit form. The Cobas-Fara was programmed to carry out pretreatment of the sample with ascorbate oxidase before addition of the cholesterol colour reagent.